Development of hypertension and uraemia after pyelonephritis in childhood: 27 year follow up. Issue 6701 (16th September 1989) - Jacobson, S. H.; Eklöf, O.; Eriksson, C. G.; Lins, L. E.; Tidgren, B.; Winberg, J.
Abstract : OBJECTIVE–Determination of the long term incidence of uraemia, hypertension, and toxaemia in pregnancy associated with non-obstructive focal renal scarring after pyelonephritis in childhood 25-35 years earlier. DESIGN–27 Year follow up of patients with non-obstructive focal scarring identified from a retrospective review of intravenous urograms performed in childhood between 1951 and 1967. SETTING–Paediatric primary referral centre and urological clinic in tertiary referral centre. PATIENTS–30 Patients (mean age 33 (range 22-41] with non-obstructive focal renal scarring first detected between 1951 and 1967 and a history of febrile urinary tract infection. MAIN OUTCOME MEASURE–Hypertension and complications of renal damage. RESULTS–Three patients had developed end stage renal disease, seven had developed hypertension, two of 16 women had a history of toxaemia during pregnancy, and seven patients had undergone renal surgery during follow up. Of the 20 patients who had neither had renal surgery nor had end stage renal disease, all had a significantly lower glomerular filtration rate and renal plasma flow and higher diastolic blood pressure, mean arterial blood pressure, plasma renin activity, and serum beta 2 microglobulin concentration than 13 healthy age matched controls. Diastolic blood pressure and plasma renin activity were positively correlated (r = 0.50, p less than 0.05) and so were fractional sodium excretion and both systolic and diastolic blood pressures (r = 0.54, p less than 0.01, r = 0.51, p less than 0.01 respectively). The progress of renal damage was unrelated to the incidence of recurrent infections. CONCLUSIONS–Children with focal renal scarring due to pyelonephritis are at high risk of serious long term consequences. It is essential that they are given adequate attention and care during adolescence and pregnancy.